An ABCD Program to Increase Access to Dental Care for Children Enrolled in Medicaid in a Rural County - Tarja Kaakko, DDS; Erik Skaret, DDS; Tracy Getz, MS; Philippe Hujoel, DDS, PhD; David Grembowski, Ph (Blackwell Synergy, 2002)
The Access to Baby and Child Dentistry (ABCD) Program addresses the needs of families in obtaining dental care. In this study, the program was evaluated in rural Stevens County, Washington. Aims were to assess utilization of dental services, average dental expenditures per child, and oral health status.